Alginate edible films containing essential oils: characterization and bioactive potential - Lopes, Ana I. (2025)
Essential oils (EOs) are natural substances rich in phenolic compounds with notable antimicrobial and antioxidant properties. However, they present some limitations, such as low stability and bioavailability. Incorporating EOs into polymeric films offers a novel approach to overcome these challenges while enhancing their efficacy. In this study, we produced and thoroughly characterized alginate-based edible films incorporated with five different EOs—rosemary, eucalyptus, oregano, sage, and thyme. This is the first comprehensive investigation to include this diverse range of EOs in alginate films. Their antimicrobial and antioxidant activities were also evaluated. The results demonstrated that alginate films containing EOs exhibited significant bioactive properties. Notably, the film incorporated with oregano EO completely inhibited the growth of all tested bacteria and fungi and showed the highest antioxidant activity. Based on these findings, alginate films containing EOs present promising bioactive potential and could serve as biodegradable alternatives to conventional packaging materials, reducing environmental impact. However, further studies are necessary to assess their safety profile and confirm their viability as replacements for traditional food packaging. Future research should focus on evaluating cytotoxicity, genotoxicity, and the practical application of these films in food matrices.